2018
DOI: 10.1128/msphere.00497-18
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl-Beta-Cyclodextrin Reduces Inflammatory Signaling from Monocytes: Possible Implications for Suppression of HIV Chronic Immune Activation

Abstract: Chronic immune activation is a hallmark of HIV infection and is often not controlled even in patients under antiretroviral therapy. Indeed, chronic diseases with inflammatory pathogenesis are being reported as major causes of death for HIV-infected persons. Hydroxypropyl-beta cyclodextrin (HP-BCD) is a cholesterol-sequestering drug that inhibits HIV replication and infectivity in vitro and in vivo. Recent studies have demonstrated the importance of cholesterol metabolism and content in different inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(75 reference statements)
1
11
0
1
Order By: Relevance
“…In atherosclerotic plaques, HP-β-CD increased cholesterol efflux, reducing crystal load, inflammation, and disease progression (Zimmer et al, 2016 ). Similar effects have been observed in monocytes derived from HIV-positive donors (Matassoli et al, 2018 ), and the compound has been explored clinically for treatment of Niemann-Pick disease type C1, a neurodegenerative disease characterized by excessive cholesterol and lipid accumulation (Liu, 2012 ; Ottinger et al, 2014 ).…”
Section: Macrocycles For Drug Solubilization and Deliverymentioning
confidence: 66%
“…In atherosclerotic plaques, HP-β-CD increased cholesterol efflux, reducing crystal load, inflammation, and disease progression (Zimmer et al, 2016 ). Similar effects have been observed in monocytes derived from HIV-positive donors (Matassoli et al, 2018 ), and the compound has been explored clinically for treatment of Niemann-Pick disease type C1, a neurodegenerative disease characterized by excessive cholesterol and lipid accumulation (Liu, 2012 ; Ottinger et al, 2014 ).…”
Section: Macrocycles For Drug Solubilization and Deliverymentioning
confidence: 66%
“…At the cellular level, George et al [ 56 ] assumed an anti-inflammatory property of HPβCD after showing that its presence along with plasticized poly(vinyl chloride) (PVC) reduced LPS-induced TNF-α expression in human monocyte-like U937 cells while PVC alone had no effect. Matassoli et al [ 57 ] showed that HPβCD can inhibit LPS-induced TNF-α secretion in primary human monocytes. The higher effect on reduction of IL-8 release induced by BUD at a high concentration (100 µM) as compared to the effect of BUD:HPβCD could be linked to an inflammatory effect observed at high doses of HPβCD [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to block the transmission of the virus was demonstrated by studies in mice, with vaginal application of HPβCD blocking HIV transmission by 91% (10 out of the 11 mice treated with HPβCD did not get infected following HIV exposure) [35]. Furthermore, HPβCD was shown to reduce the inflammatory response of cultured immune cells, lowering their production of interleukins (IL-10) and cytokines (TNF-α) [36].…”
Section: Hiv Managementmentioning
confidence: 99%